Correlation of Vitamin D Intake with Hemoglobin Levels in Pregnant Women - Sari, Sagita Darma; Partan, Radiyati Umi; Lestari, Peby Maulina; Liberty, Iche Andriyani (Indonesian Journal of Global Health Research, 2024)
Pregnancy anemia called " potential danger to mother and child " ( potential endanger mother and child ), increasing risk antepartum hemorrhage , postpartum hemorrhage and surgery caesarean emergency . In babies risky malformation Congenital and Low Birth Weight Infants . The incidence of pregnancy anemia in Indonesia is experiencing increase every year . By clinical anemia closely connection with vitamin D deficiency . Vitamin D plays a role in arrange distribution substance iron inside body . Objective: to analyze the correlation of vitamin D intake with hemoglobin levels in pregnant women. Method : Cross Sectional research design. The sample was pregnant women in the Gandus Palembang Health Center working area who were taken by consecutive sampling, totaling 91 people. Data analyzed using a simple liner regression test. Results: The average hemoglobin level in pregnant women was 11.49 gr / dl and the average vitamin D intake was 12.05 µg. Pregnant women who had sufficient vitamin D intake ≥ 15 µg were 9 people (10%). Pregnant women with hemoglobin levels ≥ 11 gr / dl as many as 58 people (63.7%). The results of the simple linear regression test obtained p value = 0.028 and R square value 0.053. Conclusion: there is a correlation between vitamin D intake and hemoglobin levels in pregnant women with the effect of vitamin D intake on hemoglobin levels of 5.3%.